Development of a desktop freehand 3-D surface reconstruction system - Lim, Kim Chuan; Manuel, Boissenin; Balasumdram P., Amavasai; Reza, Saatchi (2008)
This paper discusses the development of a freehand 3-D surface reconstruction system. The system was constructed by making use of readily available off-the-shelf components, namely a laser line emitter and a webcam. The 3-D laser scanner system allows the user to hand sweep the laser line across the object to be scanned. The 3-D surface information of the object is captured as follows. A series of digital images ofthe laser line, generated by the intersection of the laser plane, the surface of the object and the background planar object were captured and stored in a PC. The points on the laser line were extracted. The 2D laser points that were found on the surface of the planar object were projected onto the 3-D space using a pinhole camera model. The laser plane was calibrated. Using the 2-D laser points found on the surface of the 3-D object, a cloud of 3-D points which represent the surface of the object being scanned was generated by triangulation. For the laser plane calibration two different methods were implemented. Their performance were compared.